A new species of the rare monotypic genus Cyrtinoclerus Chapin from Borneo, with notes on Meprinogenus Kolibáč (Coleoptera: Thanerocleridae) - Kolibáč, Jiří (Zootaxa, 2023)
Cyrtinoclerus sabahensis sp. nov. of the less diverse cleroid family Thanerocleridae is described from Borneo. The unique specimen was found in the Malaysian state of Sabah and represents the first collecting record of the genus in one hundred years. The new species is assigned to the hitherto monotypic genus Cyrtinoclerus Chapin, 1924, whose single species is known from a single specimen from Basilan, Philippines, with no subsequently collected specimens known to date. Cyrtinoclerus is distinct in its unique synapomorphies, namely the tarsi with formula 5-5-5 but tarsomeres 4 reduced in size, elytron depressed in basal third with distinct bulge, and seriate punctation of elytra. The genus is re-examined and again classified within Thanerocleridae. A systematic status of Cyrtinoclerus and its relative Meprinogenus Kolibáč, 1992, also known only from two just one-hundred-year-old specimens, is discussed and possible synonymy of the latter genus suggested. The family Thanerocleridae now comprises 38 extant species in eleven genera and four extinct Cretaceous genera and species found in Burmese and Charentese ambers. A phylogenetic analysis of all fifteen extinct and extant genera of Thanerocleridae based on 36 morphological characters is presented and updated key to the tribe Thaneroclerini provided.